If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -26 = 5x Reorder the terms: -26 + 6x = 5x Solving -26 + 6x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -26 + 6x + -5x = 5x + -5x Combine like terms: 6x + -5x = 1x -26 + 1x = 5x + -5x Combine like terms: 5x + -5x = 0 -26 + 1x = 0 Add '26' to each side of the equation. -26 + 26 + 1x = 0 + 26 Combine like terms: -26 + 26 = 0 0 + 1x = 0 + 26 1x = 0 + 26 Combine like terms: 0 + 26 = 26 1x = 26 Divide each side by '1'. x = 26 Simplifying x = 26
| 4/5x=7 | | y^2+9=2y^2+2y-12 | | -19x^2-12x^2+16x=0 | | 8x-52=4 | | -8(n-6)=5-7n | | -t/4=-3π | | x-10.4=4.6 | | 4y=4x+24 | | x+3.4=2.2 | | (5y+7)-(4+4y)=7 | | X^2+y^2+2x-6y-15=0 | | 13(x-3)=-5-8 | | 18x+3y=96 | | R+33=72 | | x=437/2 | | 5.2-3x-2=0 | | n+4.9=18.8 | | 6x-14=4x-24 | | x^2+y^2+6x-8y-8=0 | | x=437-147 | | 2.5a+17.5=1.5a-0.75 | | (2x)*(-2x)/4 | | y=12x^2-12x^3 | | X^2+y^2+12x-2y-10=0 | | .05x+.09(28000-x)=2400 | | 5+2.36+.15m=m | | 4x^3-3x+51=0 | | -2x+9y=-24 | | n+98=74 | | 42=8+K | | 4x-4=7x+8 | | -96=7x-5 |